An Enterprise Architecture in the Construction Management Software using the Business Model Canvas - Susatyo, R Wahyu Indra; Indrajit, Eko; Dazki, Erick (Politeknik Ganesha Medan, 2024)
Indonesia's construction industry has boomed over the past decade, acting as a powerful engine for the nation's economic growth. However, this success story comes with a growing list of challenges. Construction projects are becoming increasingly intricate, demanding not only efficiency and quality but also enhanced safety and a minimized environmental footprint. To tackle these complexities, the industry is undergoing a crucial transformation towards